2015
DOI: 10.1016/j.arth.2015.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Novel Three-Step Medial Release Technique in Varus Total Knee Arthroplasty

Abstract: We investigated the efficacy and safety of our novel three-step medial release technique in varus total knee arthroplasty (TKA) over time. Two hundred sixty seven consecutive varus TKAs were performed by applying the algorithmic release technique which consisted of sequential release of the deep medial collateral ligament (step 1), the semimembranosus (step 2), and multiple needle puncturing of the superficial medial collateral ligament (step 3). One hundred seventeen, 114, and 36 knees were balanced after ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Future randomized studies of these covariates may be required to decrease the issue of selection bias. Numerous studies have shown a relationship between medial release and increment of the medial tibiofemoral gap [5,6,21,27,31,42]. In the current study, gap increment according to each compartment showed that the medial flexion gap was the most-increased compartment, followed by the medial extension gap, as a progressively larger release was done.…”
Section: Discussionsupporting
confidence: 54%
“…Future randomized studies of these covariates may be required to decrease the issue of selection bias. Numerous studies have shown a relationship between medial release and increment of the medial tibiofemoral gap [5,6,21,27,31,42]. In the current study, gap increment according to each compartment showed that the medial flexion gap was the most-increased compartment, followed by the medial extension gap, as a progressively larger release was done.…”
Section: Discussionsupporting
confidence: 54%
“…For distal femoral osteotomy, the apex of the intercondylar notch was used as the intramedullary positioning rod entry point, and the appropriate valgus angle was selected according to the hip-knee-shaft angle (HKS) measured on the FLX to perform a standard distal osteotomy of 9 mm. Extramedullary test of the lower limb alignment was performed; the cruciate ligament, osteophyte, and residual meniscus tissues were removed to balance the extension gap, and appropriate lateral release was conducted if necessary as described by Kim and Ranawat [25,26]. After the extension gap was well balanced, the femoral osteotomy at the flexion position was conducted referring to the Whiteside's line, then referring to the tibial plateau osteotomy surface and the extension gap to balance the flexion gap.…”
Section: Preoperative Design and Surgical Techniquesmentioning
confidence: 99%
“…For example, 4-mm reduction osteotomy provides approximately 1.7° and 0.7° varus improvement in flexion and extension, respectively, while 8-mm reduction osteotomy only improves 2.8° and 0.9° in flexion and extension, respectively [ 15 ]. In addition, employment of a stepwise release technique could avoid unnecessary over release [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%